ANTIFUNGAL ACTIVITY OF SOUTH AFRICAN PODOCARPUS SPECIES USED IN TRADITIONAL MEDICINE - Abdillah, H.; Finnie, J.; Van Staden, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Species of Podocarpus are utilized traditionally in treating all manner of ailments in various parts of the world. In South Africa, four species of Podocarpus (P. elongatus, P. falcatus, P. henkelii and P. latifolius) are used as herbal remedies to treat both human and livestock diseases. In this study the antifungal activity of these species against Candida albicans was investigated. Petroleum ether, hexane, dichloromethane, acetone, and 80% ethanol were used in the extraction of plant material. Microdilution and M27-P-broth dilution assays were used to assess antifungal activity. All extracts exhibited significant antifungal activity with minimum inhibitory concentration (MIC) values of less than 1 mg/ml. For the M27-P-broth dilution method, extracts showed MIC values ranging from 0.13 mg/ml to 6.25 mg/ml while in the microdilution assay, extracts showed lower MIC values ranging from 0.03 to 2.34 mg/ml after 48 h. P. latifolius leaves inhibited growth of C. albicans at the lowest concentration of 0.02 mg/ml after 24 h and 0.03 mg/ml after 48 h for dichloromethane extracts and 0.02 mg/ml after 24 h and 0.04 mg/ml after 48 h for acetone extracts. At concentrations higher than 1.25 mg/ml the inhibition was fungicidal while at lower concentrations the inhibition was fungistatic for all extracts tested. In general, all four species exhibited good inhibition against C. albicans. The results obtained from our screening confirm the therapeutic potency of these four species and thus provide a rationale for their use in traditional medicine.